FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN PRAKTIK MEROKOK PADA MAHASISWI S1 UNIVERSITAS DIPONEGORO SEMARANG - Oktalia Liviyana; Priyadi Nugraha P.; VG Tinuk Istiarti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
According to a report from Riskesdas in 2007, it was known that the prevalence of smoking on women about 5,2% increased to 6,7 % in 2013 and it is believed as a serious problem for threatening woman’s reproduction health. Smoking most occurs among college students (late teens aged 18-24). However, they should not do smoking since they are considered to have a role as the agent of change, social controller, and intellectuals. This research is aimed to find out the factors which are associated to smoking on undergraduate students of Dipenogoro university.This research is analytical descriptive with quantitative approach. There are 100 respondents from FISIP, FH, and FEB at dipenogoro university as the sample by using quota sampling. The data were collected through interview by using questionnaire. Data analysis was done univariately and bivariately. Some respondents are people who are 20 years old (45%), come from outside Semarang (86%), have monthly allowance more than two millions (62%), and have smoked more than 3 years (61%), also Malboro Ice Blast is the most consumed cigarette by the respondents (19%). Almost 74% respondents smoke in high frequency. The related variables to smoking on students are, allowance (p=0,020), smoking period (p=0,000), respondents’ attitude (p=0,008), the ease of getting cigarette (p=0,006), peers’ support (p=0,008), and parents’ acceptance (p=0,006).This research is expected to be an input to prevent the increasing number of smoking on women particulary college students.